القياس عند الإمام الشافعي: دراسة تأصيلية وتطبيقية في المعاملات المالية - Khairil Anwar Jufri (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
Qiyas or analogy has great impact on the development of shari'ah rulings, that is why according to the usuliyyin, the issue of qiyas is considered one of the most important issues in Islamic jurisprudence. In addition, qiyas is also considered as an agreed and valid evidence in ijtihad among the usuliyyin. However, even though they agreed upon the validity of qiyas, practically they differed in terms of their dependence on this source. Imam Shafi'e in his madhhab was more dependent on qiyas; he is considered as the first scholar who spoke about qiyas sufficiently. This study has every intention of explaining qiyas according to the views of Imam Shafi'e and its application in financial transactions. The study starts with the explanation of valid evidence according to Imam Shafi'e in ijtihad, which are Qur'an, Sunnah or prophetic traditions, ijma' or consensus, and qiyas. The researcher focused on each and every one of these four evidence for its definition and its validity according to Imam Shafi'e. The study ends with the explanation of qiyas's implementation according to Imam Shafi'e in developing financial transaction rulings; both are manufacturing sales or bai' al-istisna' and monetisation contract or Naqdu al-tawarruq. The study is limited to their definitions, types, rules in Shafi'e school of thought and their applications in contemporary Islamic banks. This study originated from Imam Shafi'e's book called “al-Risalah” for its theoretical aspect and based on his other book named “al-Umm” for its practical aspect. In this study the researcher used an inductive approach in order to achieve Imam Shafi'e's views and Shafi'iniyyah's views regarding the topic. The researcher also adopted the descriptive and analytical approaches to examine these view in order to acquire the findings of the topic.